DESIGN AND DEVELOPMENT OF ERGONOMIC TABLE AND ANALYZE USING RULA ANALYSIS - Mohd Hidayat Ab Rahman; Nurul Ain Maidin; Umi Hayati Ahmad; Mohd Salahuddin Mohd Basri; Mohd Nazri Ahmad; Ridhwan Jumaidin; Mohd Hairizal Osman; Mohammad Khalid Wahid (Malaysian Journal of Public Health Medicine, 2020)
Ergonomics and design have made the greatest relation in producing an artifact or creating a workplace. A computer table is widely used in classrooms in universities. However, the problems of the current computer table have been detected through the results of RULA analysis. In this project, a survey of the questionnaire was done and the anthropometric data have also been collected. The dimensions of the current computer table are then collected and the deficiencies of the current computer table have been focused on RULA analysis. A new structural design of the computer table has been designed, in order to meet the requirements of ergonomics. A product of the new design of ergonomics computer table is made and has been focused on RULA analysis to define the improvement between both tables. The paper showed a comparison between the current computer table and the new ergonomics computer table were analyzed. The improvement of the new ergonomics computer table was identified and reduced the injuries and disorders. A further investigation on better working posture when using a computer table is required, while further improvement for the product design of a new ergonomics computer table is needed, as well as the application of the ergonomics design aspect in our life.